BRAFV600E Mutation in Papillary Carcinoma Thyroid - M S, Bhuvitha; G, Krishna (Annals of Pathology and Laboratory Medicine, 2022)
Background: Thyroid malignancies comprise 1 % of total human malignancies, Papillary Thyroid Carcinoma (PTC) is the most common malignant tumour of thyroid cancers. It is estimated that 80 % of thyroid malignancies are comprised of papillary carcinoma thyroid, which shows increased incidence in women. The most important etiology of PTC is mutation of RET/RAS/BRAF which activates MAPK signaling pathway. The BRAF V600E activating point mutation appears to be highly specific for PTC. Methods: It is cross sectional study of 56 cases studied in the Government Medical college, Thiruvananthapuram, Kerala. Consecutive cases of histo-pathologically proven cases were selected and Immunohistochemical (IHC) studies for BRAFV600E were conducted, and results were recorded. Result: Our study showed female preponderance and equal distribution of cases above and below 45 years of age. Size of the primary tumour was more than 1cm for majority of cases. In our study out of 56 cases studied 45 patients showed BRAFV600E expression comprising of 80% positivity. A 44% of the total cases studied showed lymph node metastasis. Conclusion: We conclude in our study that BRAFV600E mutation is most common mutation in primary PTC patients. BRAFV600E expression most seen in elderly patients and shows strong association with lymph node metastasis. IHC assay is a reliable method to detect BRAFV600E mutation in PTC and can be used as alternative to molecular methods on routine practice